2016
DOI: 10.1152/ajpregu.00052.2016
|View full text |Cite
|
Sign up to set email alerts
|

Identifying immune mechanisms mediating the hypertension during preeclampsia

Abstract: Preeclampsia (PE) is a pregnancy-associated disorder that affects 5-8% of pregnancies and is a major cause of maternal, fetal, and neonatal morbidity and mortality. Hallmark characteristics of PE are new onset hypertension after 20 wk gestation with or without proteinuria, chronic immune activation, fetal growth restriction, and maternal endothelial dysfunction. However, the pathophysiological mechanisms that lead to the development of PE are poorly understood. Recent data from studies of both clinical and ani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
93
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 83 publications
(96 citation statements)
references
References 119 publications
(159 reference statements)
2
93
0
1
Order By: Relevance
“…Nonetheless, immunologic and inflammatory factors play important roles in the development of this disease, and the first contact between a women's immune systems and an abundance of nonself antigen that comes from the fetus could activate those factors. 12,13 The present study cohort had a high incidence of severe preeclampsia, which was diagnosed when clinical or laboratory findings suggested organ failure, imminent onset of eclampsia, or elevated blood pressure. The use of proteinuria as the selection criteria could, therefore, have led to bias as women with mild term pre-eclampsia often undergo delivery without assessment of a 24-hour urine sample.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Nonetheless, immunologic and inflammatory factors play important roles in the development of this disease, and the first contact between a women's immune systems and an abundance of nonself antigen that comes from the fetus could activate those factors. 12,13 The present study cohort had a high incidence of severe preeclampsia, which was diagnosed when clinical or laboratory findings suggested organ failure, imminent onset of eclampsia, or elevated blood pressure. The use of proteinuria as the selection criteria could, therefore, have led to bias as women with mild term pre-eclampsia often undergo delivery without assessment of a 24-hour urine sample.…”
Section: Discussionmentioning
confidence: 97%
“…The pathophysiologic mechanisms of pre‐eclampsia are unclear. Nonetheless, immunologic and inflammatory factors play important roles in the development of this disease, and the first contact between a women's immune systems and an abundance of non‐self antigen that comes from the fetus could activate those factors …”
Section: Discussionmentioning
confidence: 99%
“…; LaMarca et al. ). Our group has previously demonstrated that depletion of NK cells in the RUPP model improves both maternal and fetal outcomes (Elfarra et al.…”
Section: Introductionmentioning
confidence: 98%
“…; LaMarca et al. ; Taylor and Sasser ). In contrast to normal pregnancy, many studies have shown that NK cells in the decidua of preeclamptic women are composed of a higher cytolytic NK (cNK) cell population and a predominance of pro‐inflammatory T H 17 cells along with a corresponding decrease in T Reg number and function (Prins et al.…”
Section: Introductionmentioning
confidence: 99%
“…Potential etiological factors for this complication of pregnancy include poor placentation, excessive maternal inflammation and immune response, and endothelial dysfunction . Several studies have reported that an exaggerated inflammatory response and an imbalanced immune response together play important roles in the development of pre‐eclampsia …”
Section: Introductionmentioning
confidence: 99%